Nomogram-based prediction of growth retardation in pediatric deletional α-thalassemia: Evidence from the Mekong Delta, Vietnam - Bui, Nghia Quang; Tran, Ngoc Bich; Ta, Tram Van; Duong, Linh My; Pham-Thi, Ngoc-Nga; Nguyen, Vinh The; Tran, Ly Cong (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Growth retardation is a common complication in children with deletional α-thalassemia. Limited epidemiological data exist on growth retardation in α-thalassemia patients from low-resource settings such as Vietnam. This study investigates the prevalence and associated factors of growth retardation in pediatric patients with α-thalassemia to inform targeted interventions. Methods: A multicenter cross-sectional study was conducted involving children with confirmed deletional α-thalassemia from August 2022 to June 2023. Clinical, laboratory, and genetic data were analyzed to identify predictors of growth retardation. Results: Growth retardation affected 17.1% of the study population. Key predictors included splenomegaly ≥ grade II (OR = 12.5; 95% CI, 1.69–92.25; p = 0.013), hemoglobin levels <7 g/dL (OR = 7.67; 95% CI, 1.12–52.32; p = 0.038), and having siblings with thalassemia (OR = 13.5; 95% CI, 1.57–115.9; p = 0.018). A predictive nomogram was developed, demonstrating excellent discrimination with an area under the curve of 0.92 (95% CI, 0.82–1.0; p = 0.001) and good calibration (Hosmer–Lemeshow test, χ2(df) = 0.139 (1); p = 0.709). Conclusions: This study highlights the prevalence and associated factors of growth retardation in pediatric patients with α-thalassemia in the Mekong Delta, Vietnam. By identifying key predictors and developing a practical predictive tool for early risk assessment, these findings provide a foundation for targeted interventions aimed at improving clinical outcomes, particularly in resource-limited settings.